ChemInform Abstract: Catalytic Asymmetric [4 + 2] Annulation Initiated by an Aza‐Rauhut—Currier Reaction: Facile Entry to Highly Functionalized Tetrahydropyridines. Issue 3 (22nd January 2013) - Shi, Zugui; Yu, Peiyuan; Loh, Teck‐Peng; Zhong, Guofu
Abstract Aminophosphine catalyst derived from a natural amino acid is applied to catalyze the title reaction affording enantioenriched tetrahydropyridines in high dia‐ and enantioselectivities.